2015
DOI: 10.4236/ajps.2015.64054
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Water Productivity of Drip-Irrigated Potato under Different Nitrogen Levels and Irrigation Regime with Saline Water in Arid Tunisia

Abstract: Field studies were conducted on a sandy soil during autumn of 2010 and 2011 in an arid region of Tunisia to investigate the effects of nitrogen and irrigation regimes with saline water on yield and water productivity (WP) of potato (Solanum tuberosum L. cv. Spunta) and soil salinity. For the two years, irrigation treatments consisted in water replacements of cumulated crop evapotranspiration (ETc) at levels of 100% (I100, full irrigation), 60% (I60) and 30% (I30), when the readily available water in I100 treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
3
21
2
1
Order By: Relevance
“…In addition, findings by Abdullah and Ahmed (1990) indicated that tuber number per plant increased with low salinity concentration and decreased with increasing salinity concentration. Moreover, potato tuber yield varied widely under different amounts of water, applied with different EC of water through drip irrigation at different levels (El Mokh et al, 2015). In this study, the lowest yield was 34.12 t ha -1 at a SWQI 79.63% and the highest yield was 37.79 t ha -1 at a SWQI 30.93%.…”
Section: Soil and Water Analysismentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, findings by Abdullah and Ahmed (1990) indicated that tuber number per plant increased with low salinity concentration and decreased with increasing salinity concentration. Moreover, potato tuber yield varied widely under different amounts of water, applied with different EC of water through drip irrigation at different levels (El Mokh et al, 2015). In this study, the lowest yield was 34.12 t ha -1 at a SWQI 79.63% and the highest yield was 37.79 t ha -1 at a SWQI 30.93%.…”
Section: Soil and Water Analysismentioning
confidence: 60%
“…Van Hoorn et al (2002) grew potatoes in tanks filled with loam and clay and irrigated with water of three different levels of salinity; water efficiency of potatoes was not affected by soil and water salinity. El Mokh et al (2015) showed that potato tuber yield varied widely under different amounts of water that was applied with different EC through drip irrigation at different levels. A higher salinity associated with deficit irrigation caused significant reductions in tuber yield and its components.…”
Section: Introductionmentioning
confidence: 99%
“…Iernaa and Mauromicale [8] applied deficient irrigation and increased water productivity. El-Mokh et al [6] obtained the highest yield under supplementary irrigation, while Bélanger et al [13] found that irrigation increased the weight per tuber.…”
Section: Water Utilization Efficiency (Wute)mentioning
confidence: 99%
“…In addition, Badr et al [20] stated that the full irrigation of potato resulted in the highest tuber yield with different investigated N levels used in their study, while a significant decrease in the tubers yield occurred in plants irrigated with low amounts of irrigation water. Moreover, El-Mokh et al [6] reported that irrigation with 100% ETc + 300 kg N ha −1 resulted in the highest potato tuber yield. However, Yuan et al [10] and Onder et al [54] reported a significant reduction in the tuber yield with decreasing levels of applied water.…”
Section: Yield Of Potato Tubersmentioning
confidence: 99%
See 1 more Smart Citation